Engineering singlet and triplet excitons of TADF emitters by different host‐guest interactions - Wei Zhang; Jie Kong; Rui Zhi An; Jiachen Zhang; Yujie Zhou; Lin‐Song Cui; Meng Zhou (Aggregate, 2024)
Abstract Understanding the host‐guest interactions for thermally activated delayed fluorescence (TADF) emitters is critical because the interactions between the host matrices and TADF emitters enable precise control on the optoelectronic performance, whereas technologically manipulating the singlet and triplet excitons by using different kinds of host‐guest interactions remains elusive. Here, we report a comprehensive picture that rationalizes host‐guest interaction‐modulated exciton recombination by using time‐resolved spectroscopy. We found that the early‐time relaxation is accelerated in polar polymer because dipole‐dipole interaction facilitates the stabilization of the 1CT state. However, an opposite trend is observed in longer delay time, and faster decay in the less polar polymer is ascribed to the π‐π interaction that plays the dominant role in the later stage of the excited state. Our findings highlight the technological engineering singlet and triplet excitons using different kinds of host‐guest interactions based on their electronic characteristics.